Pengaruh Penambahan Soil Stabilizer Sebagai Bahan Stabilitas Tanah Lempung dengan Pengujian Standard Proctor dan Unconfined Compressive Test - Martini, R.A. Sri; Hartini, Hartini; Agusri, Erny; Natasya, Travela Virnanda; Khanza, Ayu Kamila (Universitas Muhammadiyah Palembang, 2025)
The clay soil used in this study came from Tebing Kawat Village, Talang Ubi District, Pali Regency, South Sumatra Province. The soil sample used was disturbed soil. Soil Stabilizer was used as a mixture to increase the bearing capacity of the soil with a mixture variation of 0%, 6%, 12%, and 18% with a curing time of 0, 7, 14 days in the compaction test (standard proctor) and unconfined compressive strength (unconfined compressive test). Soil property index tests include water content (w), specific gravity (Gs), liquid limit (LL), plastic limit (PL), sieve analysis soil volume weight test mechanical tests include compaction tests (standard proctor) and unconfined compressive strength tests (unconfined compressive test). From the test results obtained the value of the original soil water content of 37.87% the value of the water content after being given a mixture of 28.71%, 19.865%, 13.66%, the specific gravity of the original soil 2.59, the specific gravity after being given a mixture of 2.62, 2.67, 2.74, the liquid limit of the original soil was obtained 48.89 after being given a mixture to 46.67, 43.49, 39.06, while the plastic limit test of the original soil 38.83 given a mixture decreased 32.72, 26.12, 17.84. The results of the sieve analysis of the percentage passing sieve No. 200 with the addition of soil stabilizer made the soil condition granural while the saturation and porosity values were 111.60% and 42.90%, meanwhile the results of the maximum dry volume weight compaction test at 14 days of curing time were 1.452 with a mixture of 18% and the optimum water content decreased by 37.53% to 27.53% with a mixture of 18%, the qu value was 1.9425 and cu was 0.97125 at a mixture of 18%.